Application of different wind field models and wave boundary layer model to typhoon waves numerical simulation in WAVEWATCH III model. Issue 1 (1st January 2019) - Qiao, Wenli; Song, Jinbao; He, Hailun; Li, Funing
Abstract: Taking severe typhoon Kalmaegi (2014) as an example, which is chosen due to its good availability of observations from mulitplatforms, the application ability of different wind field models and wave boundary layer model (WBLM) are investigated simultaneously in WAVEWATCH III model (WW3). First, based on the comparisons between measurements of two in situ buoys and model results, a better-quality wind forcing from WRF's output stands out slightly compared with other two constructed wind fields during the time segment of "During-TY". Second, the comparisons of simulated results by using different drag coefficient schemes between WBLM and the original parameterisation formula in ST2 package are further implemented. The good performance of drag coefficient C d from WBLM under high-wind conditions, which is embedded into ST2 wind-input source function, is also verified by several data set of field observations. As a result, on the basis of the observations from buoy-based and radar altimeter measurements (RAs), the values of significant wave height ( H s ) from simulation with WBLM are weaker at high sea state areas ( H s > 6   m ) compared with that from the ST2 scheme, which coincide with the general knowledge that the amount of momentum exchange at the air-sea interface plays a vital role in the development of typhoon waves. Limited by less frequently sampled collocated measurements under high-wind conditions, the effectiveness of improvement for typhoon waves simulation using WBLM in WW3 requires more validation cases in future work.